Effect of Drying Temperature on Quality of Dried Red Ginger (Zingiber Officinale Var. Rubrum) - Addiena Syahvina Nasution; Rokhani Hasbullah; Edy Hartulistiyoso (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Red ginger is a source of herbal medicines that contain phenolic compounds. The advantage of red ginger as an herbal medicine requires proper handling and treatment so that the phenolic compounds in red ginger are not damaged. Drying is the right method for obtaining red ginger extract. The aims of this study were to investigate the effect of temperature on the proximate composition of dried red ginger and to investigate the suitable temperature for drying red ginger. Red ginger drying was carried out at various temperatures (40, 50, and 60 °C). The simplicia of red ginger was then mashed and sieved. Measurement of the quality of the simplicia included yield, moisture content, ash content, fat content, protein content, crude fiber content, and carbohydrate content. Dried red ginger was observed that all parameters examined were affected by drying at various temperatures except for ash content. The result of drying temperature at 50 °C showed a better quality of dried red ginger based on yield (17,64%), moisture content (6,88%), protein content (1,80%), and crude fiber content (1,86%). Keywords: Drying, Proximate, Red ginger, Simplicia, Yield.